MODELS OF THE DEVELOPMENT OF LOCAL SELF-GOVERNMENT AND THE EXPERIENCE OF DECENTRALIZATION: AN INSTITUTIONAL APPROACH - Muminov, Nozim Muminov (International Journal of Psychosocial Rehabilitation, 2020)
The authors of the article considere the experience of decentralization of government in the countries of Eastern Europe and some other countries. Also models of the development of local self-government were presented.